2015
DOI: 10.1186/s12948-015-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Choosing wisely: practical considerations on treatment efficacy and safety of asthma in the elderly

Abstract: The prevalence of asthma in the most advanced ages is similar to that of younger ages. However, the concept that older individuals may suffer from allergic asthma has been largely denied in the past, and a common belief attributes to asthma the definition of “rare” disease. Indeed, asthma in the elderly is often underdiagnosed or diagnosed as COPD, thus leading to undertreatment of improper treatment. This is also due to the heterogeneity of clinical and functional presentations of geriatric asthma, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 110 publications
0
24
0
4
Order By: Relevance
“…Of note, in our study population, around one out of three patients (27.6%) was older than 65 years. As highlighted by other reports (28,29) asthma in the elderly is not a rare disease, and its detection and management in that specific population deserves the highest consideration. Furthermore, the treatment choices should be carefully evaluated was prevalent (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 93%
“…Of note, in our study population, around one out of three patients (27.6%) was older than 65 years. As highlighted by other reports (28,29) asthma in the elderly is not a rare disease, and its detection and management in that specific population deserves the highest consideration. Furthermore, the treatment choices should be carefully evaluated was prevalent (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 93%
“…Seventy five deaths of asthmatic patients in a recent study using home nebulizers were reported, 16-30% of them had delay in seeking help, because of over reliance on high doses of salbutamol. The exact mechanism of death in such cases is unknown, but has been postulated to be due to fatal cardiac arrhythmias induce by hypoxia (Holt, 2007), an alternative hypothesis is that inhalation of high dose beta2-agonist induced hypokalemia may further aggravated by the acute stress of the illness and by concomitant corticosteroids or theophylline therapy, so accurate detection of this side effect is useful (Scichilone et al, 2015). There are several studies that demonstrate a statistically significant decrease in serum potassium and magnesium after β2AR agonists administration.…”
Section: β2-adrenoceptor Agonists (B2ar)mentioning
confidence: 99%
“…Было показано, что АЛП безопасны у пожилых пациентов с БА, хотя описаны единичные случаи острого гепатита и возникновения синдрома Чардж -Стросса. Остается открытым вопрос, являются ли эти реакции случайными и связаны ли они с возрастом [53].…”
Section: ба у пожилых пациентовunclassified